Cause-related marketing influence on consumer loyalty in a medium-sized city - Molinillo, Sebastian (2020)
The purpose of this study is to analyze the e ect of the performance of a cause-related marketing action on consumer loyalty by a company. In addition, the study explores the moderating e ect of the publicizing medium. The proposed theoretical model was tested based on data gathered from a face-to-face questionnaire completed by 421 respondents living in a medium-sized city. The results validated the proposed model and showed that the functional and image fit between social actions and companies are key antecedents of perceived corporate ability (CA) and company credibility. It was shown that CA directly influences customer satisfaction, that credibility indirectly influences customer satisfaction through perceived corporate social responsibility, and that satisfaction directly and positively impacts customer loyalty. Moreover, the influence of functional and image fit in the model were shown to be moderated by the type of publicizing medium. Specifically, the e ect of functional fit on corporate ability is greater for traditional media (TM) than for social media (SM). On the other hand, the e ect of image fit on corporate ability is greater for SM than for TM. The theoretical and practical implications of these results are discussed.